Mitochondrial uncoupling protein 1 expression in thymocytes. - Fallon, Padraic; Porter, Richard (My University, 2008)
Using an antibody specific and selective to mitochondrial uncoupling protein 1 (UCP1) peptide, this study confirms the observation that UCP 1 is present in thymocytes isolated from UCP 1 wild-type, but not UCP 1 knock-out mice. UCP 1 is also shown to be present in thymocytes isolated from rat. It was also demonstrated that an antibody raised to the full-length UCP 1 protein appears to be non-specific for UCP 1, as it detects protein in UCP 1 wild-type and UCP 1 knock-out mice, protein in mitochondria isolated from brown adipose tissue of both UCP 1 wild-type and UCP 1 knock-out mice, as well as detecting protein in mitochondria isolated from rat spleen, kidney, skeletal muscle and liver, tissues that do not express UCP 1. We were also able to show that CIDEA, a soluble protein with a suggested role in regulating UCP 1 function, is equally abundant in thymocytes from UCP 1 wild-type and UCP 1 knock-out mice. Taken together our data demonstrate that (a) UCP 1 is present in rat and mouse thymocytes, (b) that the antibody to full-length UCP 1 is not specific for UCP 1 and (c) that the absence of UCP 1 does not affect native expression of CIDEA in thymocytes.
PUBLISHED
PubMed ID: 18471433
Keywords: Thymocytes; Uncoupling protein-1; Thymus; Mitochondria; UCP 1 knock-out mice; Confocal microscopy; Immunology, Inflammation & Infection